Repositioning Delegated Authority and Binding Power of Ministerial Regulations in Indonesia - Risky, Saiful; Al-Fatih, Sholahuddin; Esfandiari, Fitria; Anoraga, Surya (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research examines the position and binding power of Ministerial Regulation (Permen) and Coordinating Ministerial Regulation (Permenko) in Indonesia, after the Job Creation Law (Law No. 6/2023). The formulation of the problem includes (1) how the legal construction of Permen as a form of delegated legislation is, and (2) how is the coordinative nature and normative position of Permenko in the hierarchy of national regulations. The method used doctrinal analysis of positive legal norms combined with legislative delegation theory and public administration theory on coordination. The main findings reveal that the effectiveness of Permen depends on the clarity of delegation clauses and enforcement mechanisms, while the effectiveness of Permenko is determined by (a) clarity of delegation, (b) inclusion of sanction provisions, (c) layering regulation through supporting government regulation/presidential regulation, (d) participatory drafting mechanisms, and (e) accountability mechanisms such as reporting clauses and judicial review. This research contributes by formulating an integrated normative blueprint for the design of Permenko that integrates legal and administrative elements, as well as recommendations for amending Law No. 12/2011 and issuing supporting regulations. The implications of the study include strengthening legal legitimacy, increasing bureaucratic compliance, and improving checks and balances mechanisms in the delegation of executive authority. With the implementation of this blueprint, Permenko are expected to become a strategic instrument to ensure the consistency of national public policies, strengthen the principle of constitutionalism, and realize good governance in Indonesia.Keywords: Binding Power, Delegated Authority, Ministerial Regulations, Normative Hierarchy AbstrakPenelitian ini mengkaji kedudukan dan daya ikat Peraturan Menteri (Permen) dan Peraturan Menteri Koordinator (Permenko) di Indonesia pasca UU Cipta Kerja (UU No. 6/2023). Rumusan masalah meliputi (1) bagaimana konstruksi hukum atas Permen sebagai salah satu bentuk delegasi peraturan perundang-undangan, dan (2) bagaimana sifat koordinatif dan kedudukan normatif Permenko dalam hierarki peraturan perundang-undangan nasional. Metode yang digunakan adalah analisis doktrinal norma hukum positif yang dipadukan dengan teori delegasi peraturan perundang-undangan dan teori administrasi publik tentang koordinasi. Temuan utama penelitian ini adalah, bahwa efektivitas Permen tergantung pada kejelasan klausul delegasi dan mekanisme penegakannya, sedangkan efektivitas Permenko ditentukan oleh (a) kejelasan delegasi, (b) pencantuman ketentuan sanksi, (c) pelapisan peraturan melalui peraturan pemerintah/peraturan presiden pendukung, (d) mekanisme penyusunan partisipatif, dan (e) mekanisme akuntabilitas seperti klausul pelaporan dan uji materiil. Penelitian ini memberikan kontribusi berupa penyusunan cetak biru normatif terpadu untuk perancangan Permenko yang mengintegrasikan unsur hukum dan unsur administratif, serta rekomendasi untuk melakukan amandemen terhadap UU No. 12/2011 dan penerbitan peraturan pendukung. Implikasi dari penelitian ini antara lain penguatan legitimasi hukum, peningkatan kepatuhan birokrasi, dan perbaikan mekanisme checks and balances dalam pendelegasian kewenangan eksekutif. Dengan diimplementasikannya cetak biru ini, Permenko diharapkan dapat menjadi instrumen strategis untuk menjamin konsistensi kebijakan publik nasional, memperkuat asas konstitusionalisme, dan mewujudkan tata pemerintahan yang baik di Indonesia.Kata kunci: Kekuasaan Mengikat, Kewenangan yang Didelegasikan, Peraturan Menteri, Hirarki Normatif